GREEN IS THE NEW BLACK: THE ROLE OF GREEN MARKETING AWARENESS AND PERCEIVED INNOVATION IN THE FAST FASHION INDUSTRY - Gabrielle Dione Tulangow; Kunthi Afrilinda Kusumawardani (President University, 2021)
The purpose-driven strategy has become one of the tactics used by companies as a competitive advantage to attract the market. The growing interest of sustainability and ecofriendly products can be seen among the younger consumer's behaviour, which indicated the increase of their awareness of the recent phenomena. The current study examined the effect of green marketing awareness and perceived innovation on customer's purchase intention by considering the corporate image, product image, and purchase intention as the mediator in the fast fashion industry. The quantitative research method was performed with structural equation modelling (PLS-SEM) technique to examine the proposed hypothesis. A total of 307 valid responses were collected from the greater Jakarta area and tested using Smart PLS version 3. This study found that the determinants of purchase intention are social responsibility and corporate reputation. Moreover, both green marketing awareness and perceived innovation influenced corporate reputation, product image, and social responsibility. However, the product image does not influence the customer to purchase intention. The findings indicated that the customer purchase intention affected significantly by awareness of company's marketing through the social responsibility done by the company. This study provides practical implications for business to create a green marketing approach as the strategic action. Keywords: Green Marketing Awareness, Perceived Innovation, Social Responsibility, Product Image, Corporate Reputation, Purchase Intention